Returnable packaging as a sustainability factor in the automotive chain: a case study. - Akabane, Getulio K.; Bussola, Fernando José; Galhardi, Antonio César; Pozo, Hamilton; Neto, José Martino (Archives of Business Research, 2018)
Packaging makes a valuable contribution to economic, environmental and social sustainability through product protection, waste prevention, enabling efficient business conduct and providing consumers with the benefits of the products it contains. The case study chosen for the work was carried out in a multinational automotive company with the objective of researching the financial and environmental factors in the substitution of one-way packages by the returnable ones during the distribution of parts for automotive dealers. There is no single solution to manage packaging waste. The best combination of options depends on local conditions, especially demographics and the degree of investment made in modern processing systems. Determining the best combination of options for managing packaging waste therefore requires detailed case-by-case analysis where life-cycle assessments can provide valuable decision support.